Composite nonsmooth multiobjective programs with V-ρ-invexity - Reddy, L.V.; Mukherjee, R.N. (My University, 1999)
In this paper, some problems consisting of nonsmooth composite multiobjective programs have been treated with V-ρ-invexity type of conditions. In particular, we prove the generalized Karush-Kuhn-Tucker sufficient optimality theorem and duality theorems for nonsmooth composite multiobjective programs. Also, weak vector saddle point theorems are obtained for the composite programs under V-ρ-invexity conditions. The results obtained generalize the results of Hun Kuk et al. to some extent.
Keywords: Composite nonsmooth multiobjective programs; V-ρ-invexity; duality; weak vector saddle point